La investigación nacional en educación 2007 – 2011. Balance y agenda - Rodríguez-Sosa, Jorge (2013)
The report offers a perspective of national research in education with two purposes: (i) to take stock of what has been done (and not done) and, based on this, (ii) to define a research agenda 2012-2016 period. The study identifies the topics addressed with greater emphasis, the methodological guidelines employed, and the institutional frameworks in which the research was carried out. It also establishes the results achieved, the trends of those results, the gaps or omissions and what remains to be done. The research agenda identifies routes of work on those issues that were partially addressed, emerging issues and issues that were not addressed at all. The report was prepared using the results of the investigation as their main source; that is, including questions, the purposes defined, models of analysis and consolidated data to support them. Also, the report includes analytical essays on field research and consulting reports when it was estimated that they used research designs along with minimum rigor criteria. All sources were contrasted with researcher and decision maker interviews. The report first version was validated in a workshop with scholars, researchers and officials